Implementasi Pembelajaran Sosial Emosional dalam Meningkatkan Kesejahteraan dan Prestasi Peserta Didik - Indah Dwi Rahayu (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Social Emotional Learning (SEL) is a crucial educational approach aimed at holistically developing students’ social and emotional competencies. This article aims to examine the implementation of SEL in school environments to improve students’ psychological well- being and academic performance. The research method used is a literature review, which involves analyzing various scholarly journals, books, and relevant articles to identify the concepts, objectives, benefits, implementation strategies, and impacts of SEL. The findings indicate that SEL implementation significantly enhances students’ abilities to manage emotions, build positive social relationships, and improve focus and learning motivation. SEL also contributes to the creation of an inclusive and supportive learning environment. However, challenges such as limited resources, time constraints, and the need for teacher training remain obstacles to effective implementation. This article is expected to serve as a reference for educators and policymakers to effectively integrate SEL into the education system.